MTHFR Gene C677T polymorphism (rs1801133) and susceptibility to colorectal polyps in an Azerbaijani population - Aslanov, Hazi; Bayramov, Bayram; Reißfelder, Christoph; Abdullayeva, Shams; Mammadova, Zeynab; Aliyev, Fikrat; Keese, Michael; Hajibabazade, Javahir; Yagublu, Vugar (Journal of Clinical Medicine, 2024)
Background: Understanding the relationships between the methylenetetrahydrofolate reductase (MTHFR) gene polymorphism, colorectal polyps, and CRC risk can aid in advancing personalized medicine approaches in CRC prevention. The aim of the current study is to identify the association of C677T polymorphism of the MTHFR gene with the risk of colorectal polyps in the Azerbaijani population. Methods: This study included 125 patients with colon polyps and 155 healthy individuals as a control group. DNA was extracted from venous blood samples obtained from patients and healthy individuals, and the results were analyzed through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and agarose gel electrophoresis. Results: Wild-type, heterozygote, and homozygous mutant were revealed within 69 (55.2%), 49 (39.2%), and 7 (5.6%) patients and within 100 (64.5%), 45 (29%), and 10 (6.5%) healthy controls, respectively. However, no significant statistical associations were observed between CT and TT genotypes, dominant (CC vs. CT + TT) and recessive (CC + CT vs. TT) models, and the mutant T allele and disease risk. There were also no significant differences between patients and controls regarding age, sex, smoking and alcohol use. Conclusion: Our research did not reveal any significant association between the MTHFR C677T polymorphism and susceptibility to colorectal polyps in the Azerbaijan population.